Incidence of canine impaction in tribal population of Jharkhand - Awanindra K Jha; Subhash Chandra; Saurabh Mallick; Om Prakash; Vikrant Ranjan; Subia Ekram (Wolters Kluwer Medknow Publications, 2023)
Introduction: The position of the canine has a key role in facial harmony, dental aesthetics, functional occlusion, and health of temperomandibular joint. Maxillary canine impaction is the second most common tooth after third molars impaction. Maxillary canines are more prone to impaction due to longer path of eruption. Settings and Design: All the patients were examined in the Dental Chair light and referred to the department of Oral Radiology for Orthopantomogram. Yamamoto's classification was used to classify maxillary canine impaction. Position of mandibular canine from cement-enamel junction was used for mandibular canine impaction. Materials and Methods: The study was performed on 2300 patients who consulted the orthodontic department from January 2018 to July 2022. Orthopantomogram of each patient was examined for canine impaction, retained deciduous teeth, cyst, and other anomalies. The incidence and pattern of canine impaction was assessed. Statistical Analysis: The data was then statistically analyzed using Graph Pad Prism software. The incidence of impacted canine was evaluated. The effect of gender was evaluated using a t-test. Results: A total of 2300 subjects were examined out of which 52 individuals were diagnosed with canine impaction. The incidence of canine impaction among orthodontic patients is 2.26%. The amount of canine impaction in females (60%) is higher than males (40%). The ratio of canine impaction of the maxilla and mandible is 2.5. Conclusion: The incidence of canine impaction was found to be 2.26 percent in the tribal dominant population of Jharkhand. Type II (50%) pattern in the maxilla and Level A (57%) impaction in the mandible was found to be the highest.